Analisis Implementasi Kebijakan Penurunan Stunting di Desa Wamsisi Kecamatan Waesama Kabupaten Buru Selatan - Mamulaty, Arjun; Rengifurwarin, Zainal Abidin; Normawati, Normawati (Jurnal Ilmiah Global Education, 2024)
This study aims to examine and describe the implementation of stunting reduction policies and their supporting and inhibiting factors in Wamsisi Village, Waesama District, South Buru Regency. The data needed in this study was collected through interview, observation and documentation techniques. Data analysis of the results of this study used qualitative descriptive analysis techniques. The results of this study found that an implementation of stunting reduction policy in Wamsisi Village, Waesama District, South Buru Regency is in quite good condition, especially activities to monitor youth growth, provide additional food for youth, organize early stimulus for child development and provide optimal health services. This is influenced by factors of environmental conditions, the relationship between the organization and the character of the implementing institution while the less supportive factor is human resources both in terms of quality and quantity.